Metabotropic Glutamate Receptor Subtype 5 in Alcohol-Induced Negative Affect - Chelsea R. Kasten; Eleanor B. Holmgren; Tiffany A. Wills (Brain Sciences, 2019)
Allosteric modulators of metabotropic glutamate 5 receptors (mGlu5 receptors) have been identified as a promising treatment to independently alleviate both negative affective states and ethanol-seeking and intake. However, these conditions are often comorbid and might precipitate one another. Acute and protracted ethanol withdrawal can lead to negative affective states. In turn, these states are primary drivers of alcohol relapse, particularly among women. The current review synthesizes preclinical studies that have observed the role of mGlu5 receptor modulation in negative affective states following ethanol exposure. The primary behavioral assays discussed are ethanol-seeking and intake, development and extinction of ethanol-associated cues and contexts, behavioral despair, and anxiety-like activity. The work done to-date supports mGlu5 receptor modulation as a promising target for mediating negative affective states to reduce ethanol intake or prevent relapse. Limitations in interpreting these data include the lack of models that use alcohol-dependent animals, limited use of adolescent and female subjects, and a lack of comprehensive evaluations of negative affective-like behavior.